Eradication of Klebsiella pneumoniae biofilms and persister cells using silver nitrate: DOI: 10.48129/kjs.15153 - Aziz, Sarah Naji; Mohammed F. Al Marjani (Kuwait Journal of Science, 2022)
To perceive the relationship between the emergences of antibiotics persistence, biofilm formation, and to study the role of silver nitrate in fighting these microbes, a total 50 clinical Klebsiella pneumonae isolates were collected from clinical sources and identified using genotypic identification by using specific primer (rpoB gene) from housekeeping genes. Detection of their biofilm-forming abilities were carried out. The eradication effect of silver nitrate to control bacterial persistence and reducing the biofilm-forming abilities were studied. We found that 40 isolate (80%) were biofilm-formers. From bacterial persisters, (75%) were biofilm-formers. Silver nitrate showed a great role to eradicate persister cells and inhibition of bacterial biofilm formation of clinical isolates of K. pneumoniae.